Spatially interpolated PM2.5 concentrations for the US from 2019-2020 - Ford, Bonne; O'Dell, Katelyn; Pierce, Jeffrey R.; Fischer, Emily V. (Colorado State University. Libraries, 2021)
This dataset contains spatially interpolated daily PM2.5 concentrations observed by monitors in the Environmental Protection Agency's Air Quality System and non-smoke seasonal background PM2.5 estimates for 2019-2020. It is a continuation of the previous dataset: https://doi.org/10.25675/10217/230602.
US Environmental Protection Agency. Air Quality System Data Mart [internet database] available at http://www.epa.gov/ttn/airs/aqsdatamart. Accessed June 20, 2019.
Dataset produced using code written by Katelyn O'Dell for https://doi.org/10.25675/10217/230602/
This dataset contains spatially interpolated daily PM2.5 concentrations observed by monitors in the Environmental Protection Agency's Air Quality System and non-smoke seasonal background PM2.5 estimates as in https://doi.org/10.25675/10217/230602 but extended for 2019-2020. See the readme file for details on data processing and recommended usage.
Department of Atmospheric Science